Modeling of adsorption isotherms and kinetics of reactive dye from aqueous solution by peanut hull - Tanyildizi, M. Saban (Elsevier Science Sa, 2011)
Adsorption of Reactive Black 5 (RB5) in aqueous solution by peanut hull was studied by using Placket-Burman (PB) and Central Composite Design (CCD). Four out of the 7 factors (initial dye concentration, initial solution pH, amount of adsorbent, temperature, particle size, shaking speed and contact time) studied by PB design influenced the adsorption of dye. A CCD was used to develop mathematical model equation. Analysis of variance (ANOVA) showed a high coefficient of determination value (R(2)=0.95). Linear and quadratic effects of the initial dye concentration and linear effect of peanut hull quantity were demonstrated to be very significant (P < 0.05) for RB5 adsorption. The interaction between peanut hull dose and initial dye concentration showed remarkable effect on adsorption process. The equilibrium adsorption data of RB5 on peanut hull were analyzed by Langmuir and Freundlich models. The monolayer adsorption capacity (q(m)) increased from 50 to 55.55 mg/g with the increase in temperature from 20 degrees C to 60 degrees C. The kinetic data were analyzed using the pseudo-first-order and pseudo-second-order adsorption kinetic models. According to these models, the rate constants were calculated for different initial dye concentrations. It can be concluded that the experimental data are well defined with pseudo-second-order kinetic model. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Adsorption; Reactive dye; Peanut hull; Response Surface methodology